Endowment asset management : investment strategies in Oxford and Cambridge - Acharya, Shanta; Dimson, Elroy, 1947- (Oxford : Oxford University Press, 2007)
This book is a case study done of a set of major endowments. It is also an essential tool for endowment managers seeking to understand current practice and the major issues they confront. The authors have created an outstanding and very readable study that comprehends the broad range of issues in endowment management: from asset allocation to manager selection and monitoring to the challenges of connecting investment policy to the mission of the organization itself.
Acknowledgments -- List of tables -- Endowment definition -- The investment committee -- Investment objective -- Spending policy -- Asset allocation -- Investing in property -- Issues in portfolio management -- Portfolio risk -- Consultant selection and monitoring -- Manager selection and monitoring -- Socially responsible investment -- Performance measurement -- Endowment management cost -- Fund-raising: role of gifts -- Concluding observations -- Notes -- Bibliography -- Index.
Includes bibliographical references (p. 351-353) and index.
rpm 21/05/13
Loans
Keywords: University of Cambridge -- Endowments; University of Oxford -- Endowments; Institutional investments -- England